Q: X plus 3 - x

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

X2+3x+x+3=x(x+1)+3(x+1)=(x+3)(x+1)

x + x + 1 + x + 2 + x + 3 = -144x + 6 = 144x = 8x = 2

(x+3)(x+4) = x²+7x+12

x + 3 + 10 = x + 13

It is: x^2 -9 = (x +3)(x -3)

Related questions

It is 123.99

When x = 3, 3 plus x = 6.

X2+3x+x+3=x(x+1)+3(x+1)=(x+3)(x+1)

9

x = 0

x + x + 1 + x + 2 + x + 3 = -144x + 6 = 144x = 8x = 2

x(x + 3) + 3(x + 3) = x2 + 3x + 3x + 9 = x2 + 6x + 9 = (x + 3)(x + 3) = (x + 3)2

X 3 plus x-142 plus x is an equation equal to x3+2x-142.

(x+5)(x+3) = x^2 +8x+15

(x+3)(x+4) = x²+7x+12

x + 3 + 10 = x + 13

6*x + 30 + 4*x = x+3; the solution is x = -3